Messor erwini sp. n., a hitherto cryptic harvester ant in the Iberian Peninsula - Orou, Noel (2023)
European harvester ants, Messor species, are important ecosystem engineers. In Catalonia (Spain), among others, the three species Messor barbarus, M. bouvieri, and M. capitatus occur. At one Catalan site, a cluster of nest samples of unknown identity was found, raising the possibility of either a hybrid lineage or a currently unexplored species in the region. The aim of this study was to test whether the newly recognized cluster represents a hybrid of M. barbarus and M. capitatus, or some form of social hybridogenesis, or an independent, hitherto unrecognised species. We addressed this question in an integrative taxonomic fashion combining evidence from microsatellites analyzed via Bayesian cluster analysis, phylogenetic analyses based on mitochondrial DNA, and multivariate exploratory and confirmatory analyses of morphometric data. The unidentified Messor ants formed a well separated entity from M. barbarus, M. capitatus, and M. bouvieri in all these analyses. These results are in line with the existence of a cryptic Messor species but not with hybridization nor social hybridogenesis. The newly detected species, which has been neither genetically nor morphologically analyzed before, is described as Messor erwini sp. n., since no name-bearing types of valid Messor taxa correspond with the morphological characteristics of the species. Discovering a hitherto unknown species from a myrmecologically well studied area nourishes expectations that further diversity of the genus Messor may await its discovery.